2015
DOI: 10.3389/fphar.2015.00233
|View full text |Cite|
|
Sign up to set email alerts
|

Inflammatory stress potentiates emodin-induced liver injury in rats

Abstract: Herbal medicines containing emodin, widely used for the treatment of hepatitis in clinic, have been reported with hepatotoxicity in individuals. A modest inflammatory stress potentiating liver injury has been linked to the idiosyncratic drug-induced liver injury (IDILI). In this study, we investigated the hypothesis that lipopolysaccharide (LPS) interacts with emodin could synergize to cause liver injury in rats. Emodin (ranging from 20, 40, to 80 mg/kg), which is in the range of liver protection, was administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…Serum enzyme levels are significant markers to determine the severity of damage to particular tissue ( Tu et al, 2015 ). CCl 4 administration cause significant increase in serum enzyme levels like AST, ALT, ALP, LDH, Albumin and decrease levels of total protein levels when compared with control animals which indicate the liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…Serum enzyme levels are significant markers to determine the severity of damage to particular tissue ( Tu et al, 2015 ). CCl 4 administration cause significant increase in serum enzyme levels like AST, ALT, ALP, LDH, Albumin and decrease levels of total protein levels when compared with control animals which indicate the liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of the correlation between PM compounds and cytotoxicity revealed that 10 compounds may be related to the hepatotoxicity of PM, 7 of which are guanidine or glucoside compounds . Hepatotoxicity could be induced by emodin at high, medium and low doses, indicating that the anthraquinones may be the basis of potential hepatotoxic effects of PM (Can et al, 2015). Studies have demonstrated obvious hepatotoxicities of emodin and rhein.…”
Section: Anthraquinonesmentioning
confidence: 99%
“…In contrast to the therapeutic effects, side effects of TCM, such as hepatotoxicity, have rarely been reported. However, accumulating evidence regarding TCM-associated oxidative hepatotoxicity was frequently addressed in recent years, particularly in paradoxical pharmacological activities of toxic and curative actions [ 12 ]. The most vital clue is the association between the initiation of TCM administration and hepatotoxicity generation and, of equal importance, to the deceleration following withdrawal.…”
Section: Introductionmentioning
confidence: 99%